Risk assessment of waterborne infections in Enugu State, Nigeria: Implications of household water choices, knowledge, and practices - Onyekachi Juliet Okpasuo; Ifeanyi Oscar Aguzie; Anunobi Toochukwu Joy; Fabian C Okafor (AIMS Press, 2020)
This research investigated the prevalence of waterborne infections (WBIs) and the risks associated with household drinking water choices, knowledge, and practices. A cross-sectional multi-stage sampling research design was employed. A well-structured questionnaire was used to sample 403 individuals representing 115 household; and stool samples collected and subjected to standard parasitic and bacterial diagnostic methods. From the 403 samples, 344 (85.4%) were positive for at least one waterborne pathogen of nine isolates: E. coli (38.0%), Giardia lamblia (35.2%), E. histolytica (33.0%), Salmonella typhi (19.9%), Proteus spp. (13.2%), Shigella dysentery (9.4%), Klebsiella spp. (7.4%), Enterobacter spp. (5.5%), and Cryptosporidium spp. (5.2%). Prevalence of WBIs was >75% in all age groups, but decreased with age. Prevalence of WBIs was >80% in all communities. Risk was not biased by gender. Odds of infection from public well (OR = 2.487; CI95: 1.296-4.774) and borehole/vendor (OR = 2.175; CI95: 1.231-3.843) users was over two times greater than non-users. Risk of WBDs was significantly reduced by 60% in sachet water drinkers (OR = 0.392; CI95: 0.217-0.709; p < 0.05). Surprisingly, river/stream water users had a significant reduced risk of WBDs than non-users (OR = 0.335; CI95: 0.150-0.749; p < 0.05). Poor hygiene was the most important determinant of WBIs; poor sanitary practice increased odds of WBIs by 400% (OR = 4.945; CI95: 2.358-10.371; p < 0.05). This study shows that most household water choices are vulnerable to contamination at many points in their journey from source to mouth; and advocates adequate provision of safe water, "point of use" household water treatment, and good storage methods to effectively curb WBIs.